DUALISME HUKUM ISLAM DI INDONESIA TENTANG NIKAH SIRI - Siti Faizah (Faculty of Sharia and Law UNISNU Jepara, 2014)
This research aims to find out how the view of Islamic law (fiqh) and Indonesian positive law towards nikah siri (the secret marriage) and the implications thereof. According to Islamic law, nikah siri that fullfils conditions and pilars is valid, since the absence of recording and publication does not lead to the cancellation of the marriage contract. Meanwhile, according to the positive law, nikah siri is invalid and not enforceable because it was not recorded at Religious Affairs Office (KUA). In addition, nikah siri also causes negative implications, especially for wife and children, both in the realm of law and social. Instead, there is huge benefit of recording and publication of marriage as the legal protection and anticipation of the injustice in the household.Keywordssecret marriage, valid, protection, fiqh, KHI (Compilation of Islamic Law) Tulisan ini bertujuan mengetahui bagaimana pandangan hukum Islam (fiqh) dan hukum positif di Indonesia terhadap nikah siri dan implikasi yang ditimbulkannya. Menurut hukum Islam, nikah siri yang sesuai dan memenuhi syarat dan rukun nikah adalah sah, karena tidak adanya pencatatan dan publikasi tidak menyebabkan batalnya akad nikah. Sedangkan menurut hukum positif, nikah siri adalah tidak sah dan tidak berkekuatan hukum karena tidak tercatat di KUA. Di samping itu, nikah siri juga berimplikasi negatif terutama bagi istri dan anak, baik dalam ranah hukum maupun sosial. Sebaliknya, sangat terasa manfaat pencatatan dan publikasi nikah sebagai perlindungan hukum dan anitisipasi terjadinya ketidakadilan dalam rumah tangga.